The Forgotten Rights - the Case for the Legal Enforcement of Socio-Economic Rights in the UK National Law - Asha James (Opticon1826, 2007)
Socio-economic rights relate to an individual’s social, economic and cultural entitlements. The International Covenant on Economic, Social and Cultural Rights 1966 enumerates the following socio-economic rights: Right to work; Right to Social Security and social insurance; Right to an adequate standard of living including adequate food, clothing, housing and to continuous improvement of the standard of living; Right to health; and Right to education. In contrast, The International Covenant of Civil and Political Rights enumerates the individual entitlements in the political and civil sphere of life – entitlement to respect for life; fair trial; private and family life; freedom of thought, conscience and religion; freedom of expression among others; many of which have been incorporated in the Human Rights Act in the United Kingdom.
Keywords: living standards; social security